2023
DOI: 10.1021/acsami.2c21990
|View full text |Cite
|
Sign up to set email alerts
|

Solid SiO2-Sealed Mesoporous Silica for Synergistically Combined Use of Inorganic and Organic Filters to Achieve Safe and Effective Skin Protection from All-Band UV Radiation

Abstract: To effectively shield the full band of ultraviolet (UV) radiation and provide desirable protection, the combination of inorganic and organic filters was often used to protect human skin from the serious harm of UV exposure. However, the incompatibility of different filters and their mutual negative effect limit the production of multifilter sunscreen. In addition, the hazard of reactive oxygen species (ROS) produced by inorganic filters after UV exposure and the skin permeability of organic filters remain unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…For example, UV-absorbing molecules are encapsulated into biocompatible polymers or nanoparticles (liposome nanoparticles, polylactic acid nanoparticles, silica nanoparticles, etc.) to reduce their toxicity. In addition, coating biocompatible materials such as cyclodextrins and polymers on inorganic particles was also an effective way to reduce the risk of sunscreens. , Surprisingly, several nanomaterials have been found to be directly used as sunscreens and achieve a certain UV protection effect. These studies showed only a slight improvement in minimizing the negative effects of traditional sunscreens, while the fundamental problems have not been solved yet, and the side effects caused by such products still pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…For example, UV-absorbing molecules are encapsulated into biocompatible polymers or nanoparticles (liposome nanoparticles, polylactic acid nanoparticles, silica nanoparticles, etc.) to reduce their toxicity. In addition, coating biocompatible materials such as cyclodextrins and polymers on inorganic particles was also an effective way to reduce the risk of sunscreens. , Surprisingly, several nanomaterials have been found to be directly used as sunscreens and achieve a certain UV protection effect. These studies showed only a slight improvement in minimizing the negative effects of traditional sunscreens, while the fundamental problems have not been solved yet, and the side effects caused by such products still pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable quantification of nanoparticles absorption, scattering, and emission activities is essential for rational materials characterization, design, and applications as these optical processes differ significantly in their causes, effects, and applications. As examples, metal oxide nanoparticles with strong scattering activities in the UV ranges has been used extensively as sun block, while plasmonic nanoparticles find utilities in biosensing due to their strong scattering in the visible to infrared wavelength range. The applications of photoactive nanoparticles, referring to chromogenic and fluorogenic nanomaterials, are even more diverse, ranging from photocatalysis, photoluminescence, photodynamic therapy, photoelectronics, and photothermal energy harvesting, just to name a few. For these applications, it is the absorbed photons, not the scattered photons, that are directly responsible for chemical reactions in photocatalysis, light emission in photoluminescence, and singlet oxygen generation in photodynamic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…7 Due to their capacity to penetrate past the epidermis of the skin, TiO 2 and ZnO NPs are incorporated into the stratum corneum, altered transcriptional patterns, and substantially enriched genes and pathways that control cell communication, apoptosis, cell proliferation/differentiation, and RNA production. 19 Coating the particles 20 cannot totally avoid photocatalytic effects, which are most prominent for anatase TiO 2 . 7 A potential solution is to use a nanofree UV filter through controlled synthesis of two-in-one porous hollow micro-UV filters.…”
Section: ■ Introductionmentioning
confidence: 99%